PENGARUH TEKNIK BUDIDAYA TERHADAP INTENSITAS PENYAKIT KARAT DAN PRODUKSI KACANG TANAH (ARACHIS HYPOGAEA L.) - Hasanah, Ratna Wylis Arief, dan Junita Barus . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2004)
Effect of cultural methods on peanut rust leaf intensity and yield. An important disease of peanut is rust leaf caused by Puccinia arachidis. It ussualy occurs with pock marked diseases. Both decreased yield up to 1,0 ton/ha (50% - 60%) compare potention yield of peanut (1,8 ton/ha). The experiment was conducted at Siraman village, Pekalongan residence, Central Lampung from June to December 2000. It applied two methods: Model A (farmers pattern) and Model B (reccomendation pattern) with three replications and four cooperator farmers. The variable were growth percentage, hight of plant, number of pod, wight of wet pod, weight of dry pod, wight of 100 granules, and leaf rot intensity. The result showed the yield of recomendation pattern better than that of farmer pattern, intensity of attacked rust leaf diseases increased from 4,58% to 27,47% on farmer pattern and increased from 3,54% to 33,55% on recomendatin pattern, Macan variety is succeptible with rust leaf diseases and decreased yield up to 41,67%.